Analysis and prediction on internal surface roughness of 316L stainless steel holes prepared by selective laser melting - LIU Zhijiang; FAN Zhou; HOU Tao; TIAN Bo; ZHANG Ziyang (Fenmo yejin jishu, 2025)
The relationship between the hole radius and printing angle of the selected laser melting 316L stainless steels and the surface roughness was studied. A theoretical model of the formed structure and surface roughness was established. The surface morphology and surface roughness of the formed parts under the different parameters were discussed. The influence factors of the surface roughness were analyzed, including the stair-stepping effect, powder adhesion, and warpage deformation. The results show that, both the hole radius and printing angle have the significant effects on the surface roughness of the samples. When the printing angle exceeds 50°, the inner surface roughness of the hole increases sharply. When the hole radius is 4 mm and the printing angle is 50°, the inner surface roughness of the hole is 7.01 μm; when the printing angle is 70°, the roughness reaches 24.53 μm. With the increase of the hole radius and printing angle, the various factors would jointly affect the surface quality of the samples. It is found that the roughness prediction effect of the mathematical model is good when the printing angle is middle and low, but there would be an obvious error when the printing angle increases to 80°. The model can achieve the accurate prediction of surface roughness to a certain extent, and provide a strong theoretical basis and technical support for the surface optimization.